Forward Freight Agreements and Market Transparency in the Capesize Sector - Theodore Pelagidis; George Panagiotopoulos (Asian Journal of Shipping and Logistics, 2019)
We investigate the connection between the trading of Forward Freight Agreements (FFAs) and its microstructure effects in the volatility of the spot freight market in the Capesize dry-bulk sector of oceangoing vessels. Conditional volatility models are used to capture the volatility effects in the freight market. A connection with the trading of FFAs is established by using dummy variables, while additional factors that affect global economy and consequently the volatility in shipping markets, West Texas Intermediate, Brent oil and S&P500 Commodity Index, are incorporated into the model. The empirical results are divided into two processes. In the first process, we isolate the effect of the FFAs in the volatility of the spot rates in the physical market, indicating that FFAs led to a rise in the volatility in the physical market for the 4 Time Charter Average (4TC) and the routes C3 and C5, increase though limited. In the second process, we identify the effect of FFAs in the asymmetric response of negative shocks or information to the volatility in the physical market. A positive impact of the FFAs was identified in the 4TC, while in the three other voyage routes examined no impact was established. The results provide complementary insights to a specific shipping market segment not examined by current literature, while identifying and enhancing our understanding of the actual volatility impact of hedging instruments to the physical market. Keywords: Transportation, Financial Markets, Derivatives Markets, Commodity Markets, Freight Rates